Adolescent idiopathic scoliosis in athletes: Is there a connection? - Kenanidis, E. I.; Potoupnis, M. E.; Papavasiliou, K. A.; Sayegh, F. E.; Kapetanos, G. A. (The Physician and Sportsmedicine, 2010)
Abstract: The potential relationship between adolescent idiopathic scoliosis (AIS) and sports is rather vague. Sports have often been considered to be a causative factor of, or a treatment option for the former, particularly among adolescent athletes who are engaged in certain athletic activities. The highly repetitive nature of sports, amenorrhea, exercise-related exerted stress on the immature spine of professional adolescent athletes, and the joint laxity that may coexist during adolescence, have also been associated with an increased incidence of AIS. The purpose of this article is to discuss the potential connection between sports and AIS by reviewing the existing literature.